Utilization of dental services in a population of Nigerian University students - E. O. Ajayi; Y. O. Ajayi (Nigerian Dental Association, 2007)
Objective: The aim of this study was to assess the utilisation of dental services among Nigerian university students. Method: A questionnaire based on modified World Health Organisation questions on utilisation was administered to 375 second-year undergraduate students of the college of medical sciences of the University of Benin to determine their utilisation of dental services. Results: The results revealed only 14.1% of the subjects had utilised dental services in the past one year with a significant higher dental care use by the females than males (p<0.01). The major reasons for visiting dentist in the past 12 months among the subjects were pain from teeth (20.8%) and the need for cleaning of teeth (18.9%). The commonest reason given for not obtaining dental care was that nothing was wrong to necessitate a visit (77.3%) while 7.5% could not afford dental treatment. There was a gender difference in self-perception of oral status with 29.9% indicated something was wrong with their teeth, gums or mouth while more than half felt nothing was wrong (p<0.05). However, 77.9% of the subjects indicated they need dental treatment or advice of which 37% wanted cleaning of their teeth. Conclusion: This study revealed low utilisation of dental services among this sample of Nigerian university students with a gender difference in utilisation. The majority of the subjects seek dental care for symptomatic reasons. The implementation of oral health education programme to improve dental awareness among the university students is recommended.